ANALYSIS OF MENTAL MODEL OF STUDENTS USING ISOMORPHIC PROBLEMS IN DYNAMICS OF ROTATIONAL MOTION TOPIC - Khasanah, N.; Wartono, W.; Yuliati, L. (Jurnal Pendidikan IPA Indonesia, 2016)
The analysis of mental models is a part of the identification of students' thoughts on the concept. Mental models analysis is conducted by conditioning the complex problems such as the isomorphic issues. The research objective is to analyze the development of students' mental models on the topic rotational motion dynamics. The study was designed with the mixed method. The design phase of the research was conducted in both quantitative and qualitative approach. The quantitative phase was performed by providing pre-test, learning, and post-test containing isomorphic problems; while qualitative phase was implemented by interview and quiz. The data were analyzed quantitatively and qualitatively. The results of the study categorizes mental models into three types, i.e. Low Mental Model (LMM), Moderate Mental Model (MMM), and High Mental Model (HMM). Based on the pre-test results, it was proved that all students used Low mental model in resolving the isomorphic problems. Using the Low Mental Model, it was found that students have misconceptions on the moment of force and moment of inertia. Mental models developed gradually from Low mental model to Moderate Mental Model and then reached the High Mental Model Mental. It was observed from the results of pre-test, quizzes, and post-test. The quiz and post-test results showed the students who used Mental Model and High Mental Model.